Inhibitory activity of propolis from Philippine stingless bees (tetragonula biroi friese) against select microorganisms - Sanchez, Nicole Angelique L.; Sabino, Noel G.; Montecillo, Andrew D.; Fajardo, Alejandro C. Jr; Cervancia, Cleofas R.; Jamora, Renard M. (Philippine journal of science)
"The antimicrobial activity of the ethanol extract of propolis (EEP) from the stingless bee, Tetragonula biroi Friese, was screened fro activity against Esherichia coli, Psedomonas aeruginosa, Bacillus sereus, Candida krusei, Staphylococcus aurens, and Penicillium chrysogenum using the disk diffudion methos and agar-well assay" - title page.